Sensory preference and detection threshold for sweet taste among undergraduate students of Health Campus, Universiti Sains Malaysia - Aziz, Nur Asyirah (Pusat Pengajian Sains Kesihatan, 2017)
Individual taste sensitivity determined the taste preference in terms of individual’s ability to perceive how sweet the food product is expected to be. Major factors contribute to the rise of obesity seen from the increased preference for sugar. Thus, this study was carried out to determine the sensory preference and detection threshold for sweet taste among Malay, Chinese and Indian undergraduate students in Health Campus, Universiti Sains Malaysia. A number of 90 students from three ethnic groups (Malay, Chinese and Indian), aged from 19 to 26 years old were conveniently selected as panellists in this sensory laboratory study. Detection threshold for sweet taste was conducted using Three-Alternative Force Choice (3-AFC) method in standard sucrose solutions. Sensory preference test was ranked using 9 point hedonic scale for sweetness in tea beverage. The results indicated that Indian students had the highest detection threshold for sweet taste (8.526mM) compared to Malay (6.462mM) and Chinese students (4.405mM). Detection threshold for sweet taste based on gender differences showed female students had lower detection threshold (5.521mM) for sweetness, compared to male students (7.211mM) that show female were more sensitive in detecting sweetness. For sensory preference ranking, Indian and Malay students preferred higher level of sweetness (7.5% w/v) in tea beverage, compared to Chinese students (2.5% w/v). Sensory preference based on gender differences showed that male and female students preferred moderate level of sweetness (7.5% w/v) in tea beverage. Ethnicity and gender among students did not show significantly difference in the sensory preference and detection threshold for sweet taste. No significant relationship observed in our study between detection threshold and sensory preference that showed individuals with higher detection threshold toward sweet taste do not necessarily imply on higher level of sugar preference. Nonetheless, it is proposed that genetic variation and early exposure and experience could alter individual sensitivity level and led to increased preference for higher level of sugar in foods.